2010
DOI: 10.1152/ajpcell.00175.2010
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional implication of a Rho kinase-dependent moesin-EBP50 interaction in noradrenaline-stimulated artery

Abstract: Ezrin, radixin, and moesin (ERM) proteins are known to be substrates of Rho kinase (ROCK), a key player in vascular smooth muscle regulation. Their function in arteries remains to be elucidated. The objective of the present study was to investigate ERM phosphorylation and function in rat aorta and mesenteric artery and the influence of ERM-binding phosphoprotein 50 (EBP50), a scaffold partner of ERM proteins in several cell types. In isolated arteries, ERM proteins are phosphorylated by PKC and ROCK with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 75 publications
3
17
0
Order By: Relevance
“…Rho kinase 1 (ROCK1) has been indirectly linked to EBP50 because it has been shown that ERM family proteins, which associate with EBP50, are substrates of ROCK1 (11,36). Because p47 phox possesses phosphorylation sites that regulate its activity, and given our present findings demonstrating p47 phox association with EBP50, we tested whether ROCK1 kinase associates with p47 phox in vascular tissues.…”
Section: Ebp50 Regulates Nox1mentioning
confidence: 89%
See 4 more Smart Citations
“…Rho kinase 1 (ROCK1) has been indirectly linked to EBP50 because it has been shown that ERM family proteins, which associate with EBP50, are substrates of ROCK1 (11,36). Because p47 phox possesses phosphorylation sites that regulate its activity, and given our present findings demonstrating p47 phox association with EBP50, we tested whether ROCK1 kinase associates with p47 phox in vascular tissues.…”
Section: Ebp50 Regulates Nox1mentioning
confidence: 89%
“…Prior reports drew our attention to a possible molecular interaction between EBP50 and p47 phox . First, EBP50's interaction with actin cytoskeletal elements (11,48,49) piqued our interest in that p47 phox is known to bind actin as it translocates to and activates the Nox catalytic core (2,(50)(51)(52)(53). Moreover, the modulatory role of protein kinase C (PKC) at key sites on both molecules suggested a possible common pathway (2,9,54).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations